Spatial Distribution of Dengue and Forecasting in South Denpasar, Bali Province, Indonesia - Purnama, Sang Gede; Subrata, Made; Kardiwinata, Pasek; Sudarmaja, Made (Universitas Udayana, 2022)
Background and purpose: The incidence of dengue hemorrhagic fever (DHF) in Bali continues to increase. A new strategy is required to control dengue in Bali. The purpose of the study is to conduct spatial mapping with a geographic information system to help determine the distribution pattern and areas at risk of DHF and to predict increasing vector density and dengue cases. Methods: A cross-sectional study was conducted in the South Denpasar Public Health Center service area from January to June 2020. It was conducted in 3 villages, including Kelurahan Sesetan (3,446 households), Sidakarya Village (2,859 households), and Kelurahan Panjer (2,907 households). A total of 191 cases of DHF were recorded during the study period. Results: Calculation of the spatial analysis of the Average Nearest Neighbor (AAN) with the value of Z score=-8.03 show a spatial pattern of the distribution of DHF cases. AAN value of 0.69 (<1) means that the pattern of spread of DHF incidence is clustered. Time series forecasting by modeling using the Autoregressive Moving Average (ARIMA) and Double Exponential Smoothing Method Routine shows that larva control efforts are predicted to affect the number of dengue cases. The pattern of the spatial distribution of cases occurs in clusters. Conclusion: There is a spatial relationship with population density. It is predicted that routine larvae control will reduce dengue cases.